Evolution of the Microstructure of a CuCr1Zr Alloy during Direct Heating by Electric Current - Miroslav Karlík; Petr Haušild; Philippe Pilvin; Denis Carron (Metals, 2021)
Round tensile test specimens of an age-hardened CuCr1Zr alloy were subjected to direct electrical current heating in a Gleeble thermal–mechanical simulator at 800 °C. The mechanical properties were monitored by the Vickers hardness test, and the changes in the grain structure were examined by light metallography. A quantitative analysis of the size and distribution of fine precipitates during annealing was carried out using transmission electron microscopy (TEM). The grain structure showed a gradient corresponding to the gradient of the temperature on the test piece. Annealing for 60 s at 800 °C resulted in a partially (~50%) recrystallized structure with new grains about 45 μm in diameter. In the as-delivered condition, TEM documented tiny (1 to 4 nm) coherent chromium precipitates inducing strain fields in the matrix. During overaging, the particles lost their coherence and gradually coarsened up to a mean diameter of 40 nm after 300 s at 800 °C. The coarsening kinetics obeys Lifshitz, Sloyzov, and Wagner’s theory.